Managing operations by a logistics company for sustainable service quality: Indian perspective. Issue 5 (2nd March 2020) - Gupta, Anchal; Singh, Rajesh Kumar
Abstract : Purpose: The purpose of this paper is to understand how logistics service providers manage their operations for sustainable service quality and operational excellence. This study is also trying to propose a framework for measuring service quality index along with some research propositions for analyzing service quality and operational excellence. Design/methodology/approach: The detailed case analysis on sustainable practices of Indian logistics service providers (LSPs) has been done on the basis of case study approach suggested by Eisenhardt (1989). After this case analysis, service quality index is evaluated for the given company based on Cleveland et al. (1989) framework. The SWOT and performance analysis of the case organization has been also done, which is further followed by development of framework and propositions for analyzing service quality and operational excellence for LSPs. Findings: It can be observed from in-depth case analysis that LSPs are making use of green practices to conserve resources for long-term sustainability. LSPs optimize their resources and use sustainable practices in the form of use of reusable and recyclable packaging materials, rain water harvesting, use of solar panels, innovations such as trucking cube, safety concern toward goods and contribution toward environment and society. Practical implications: Resources optimization and green management practices are essential for LSPs for benchmarking environmental performance and for improving service quality and operational excellence. Originality/value: This study has tried to analyze green logistics practices for sustainable service quality and proposed a framework for quantifying sustainability.